Independensi Hakim Mahkamah Konstitusi Dalam Pengujian Peraturan Perundang-Undangan Yang Terkait Dengan Kewenangannya - Agatha Jumiati (Universitas Slamet Riyadi, 2019)
The philosophy of independence of judicial power is state power that is free from all forms of intervention both from within and from outside the judicial authority, except on the basis of the power of Pancasila ideology and the 1945 Constitution. because of testing the law that regulates its existence. In addition, the Constitutional Court often decided on several cases that were deemed detrimental, deterred and reduced its duties and authorities such as the additional authority to examine laws before the amendments to the 1945 Constitution, additional authority in testing the Perppu and ultra petita.